Counting to Explore and Generalize in Text-based Games - Yuan, Xingdi; Côté, Marc-Alexandre; Sordoni, Alessandro; Laroche, Romain; Tachet des Combes, Remi; Hausknecht, Matthew; Trischler, Adam (ICML 2018, 2018)
We propose a recurrent RL agent with an episodic exploration mechanism that helps discovering good policies in text-based game environments. We show promising results on a set of generated text-based games of varying difﬁculty where the goal is to collect a coin located at the end of a chain of rooms. In contrast to previous text-based RL approaches, we observe that our agent learns policies that generalize to unseen games of greater difﬁculty.